International Students in Western Developed Countries: History, Challenges, and Prospects - Akanwa, Emmanuel E. (Journal of International Students, 2015)
Many scholars have described the various challenges international students face in Western developed countries including the United States, the United Kingdom, and Australia. Some of the challenges include differences in culture, language barriers, adjustment problems, medical concerns, pedagogical challenges, housing issues, lack of support services, and financial difficulty. This paper explores some challenges of international students and implicates the need for host universities to provide more resources and support services towards meeting international students’ academic and social needs. Aside from exploring the challenges, conflicts, and contradictions to the international student experience, and their implications to academic performance, the paper presents recommendations and suggestions to host universities on how to meet international students’ varying academic and social needs.